A escrita é livre? contribuições da poesia lírica para além das grades - Faria, Maria de Lourdes Custódio de (2016)
“The writing is free? Contributions of lyric poetry to beyond the bars”: is a research that longs to contribute, through the reading and writing of lyric poetry, to the educational formation of incarcerated students These students study at a State Center of Basic Education for Young people and Adults (Centro Estadual de Educação Básica para Jovens e Adultos – CEEBJA), located in a penitentiary in Paraná. The development of this study is supported by three specific goals: i) to work the concept of literature, lyric poetry and language resources, encouraging the student to read and comprehend poetical texts; ii) to propose pedagogical practices that help the student to write and express himself through the writing of daily life poems; iii) to encourage the student to read and write poems, comprehending the writing activity as a possibility to express himself during the teaching-learning process behind the prison bars. The research was based on theoretical assumptions that point to the humanizing role that literature plays, accordingly to what is proposed by Antonio Candido (1995), giving to the student the opportunity of learning more. That will help him develop a wider perspective of the world. The theoretical support of this work was based on intellectuals such as Michel Foucault (2013), Paulo Freire (2003), Antonio Candido (1995), G. W. Friedrich Hegel (1980), Massaud Moisés (2003), Salvatore D’Onófrio (1995), Cesare Beccaria (2009). And, to support the elaboration of our Proposal of Pedagogical Expansion, we consulted the propositions of the Método Recepcional by Maria da Glória Bordini (1993) and Vera Teixeira Aguiar (1993), combined to the Reception Theory, by Hans Robert Jauss (1994) and Wolfgang Iser (1979). Therefore, this is a bibliographic qualitative research, in which the procedures were developed through a research and action method. As a result of this didactic-pedagogical process, it is possible to notice that the classroom work with lyric poetry can happen in an didactic and spontaneous way, being useful to the humanization and emancipation of the students reached by this practice.